Ana1 helps recruit Polo to centrioles to promote mitotic PCM assembly and centriole elongation - Alvarez-Rodrigo, I; Wainman, A; Saurya, S; Raff, JW (Company of Biologists, 2021)
Polo kinase (PLK1 in mammals) is a master cell cycle regulator that is recruited to various subcellular structures, often by its polo-box domain (PBD), which binds to phosphorylated S-pS/pT motifs. Polo/PLK1 kinases have multiple functions at centrioles and centrosomes, and we have previously shown that in Drosophila phosphorylated Sas-4 initiates Polo recruitment to newly formed centrioles, while phosphorylated Spd-2 recruits Polo to the pericentriolar material (PCM) that assembles around mother centrioles in mitosis. Here, we show that Ana1 (Cep295 in humans) also helps to recruit Polo to mother centrioles in Drosophila. If Ana1-dependent Polo recruitment is impaired, mother centrioles can still duplicate, disengage from their daughters and form functional cilia, but they can no longer efficiently assemble mitotic PCM or elongate during G2. We conclude that Ana1 helps recruit Polo to mother centrioles to specifically promote mitotic centrosome assembly and centriole elongation in G2, but not centriole duplication, centriole disengagement or cilia assembly.